ANALYSIS OF HEALTH SERVICE QUALITY IN IMPROVING XYZ HOSPITAL SERVICES - Heriyanto Heriyanto; Iwan Vanany; I made Jiwa Astika (Indonesian Naval Technology College STTAL, 2022)
XYZ Hospital is a type c military hospital located in Surabaya and has the function of support and optimal healthservices for military personnel, military families, and the general public. In its implementation, there are severalproblems related to health services including a decrease in the number of patient visits, lack of human resources,and long patient service times. Therefore, it is necessary to analyze the quality of health services in improvingXYZ hospital services. Service quality (Servqual) and Importance Performance Analysis (IPA) methods are usedto measure the level of quality of health services provided to patient satisfaction. Based on the results of researchfrom 99 respondents, it shows that from the 5 dimensions of Servqual, there are positive performance gaps,namely 3 attributes E1-X7, E4-X10, A3-X27, and negative values, namely 27 attributes R2-X20, R4-X22, RE1-X12, RE3 -X14, R5-X23, A5-X60, A1-25, T4-X4, A2-X26, T1-X1, RE5-X16, R3-X21, RE7-X18, T5-X5, RE2-X13,T3-X3, E5-X11, R1-X19, R6-X24, T2-X2, A4-X28, T6-X6, RE6-X17, A6-X30, RE4-X15, E3-X9, and E2-X8. In IPA,Quadrant I has 10 attributes, namely T5-X5, RE1-X12, RE3-14, RE5-X16, RE7-X18, R4-X22, R5-X23, R2-X20,A1-X25, A5-X29 which are priority improvements health services, quadrant II 6 attributes that show maintainachievement, quadrant III 8 attributes are considered less important for patients and the services obtained areconsidered normal and quadrant IV 6 attributes. considered less important for patients but the services providedare too excessive.Keywords: Quality of Health Services, SERVQUAL, IPA, XYZ Hospital.